The Impact of Regulation on CSR: An Assessment of CSRD Compliance and the Implications of the Omnibus Regulation - Čufar, Matic; Primec, Andreja; Belak, Jernej (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Aim: The research paper focuses on the analysis of sustainability regulation and its impact on corporate sustainability reporting in practice. In particular, it examines in detail the extent to which the CSRD influences corporate sustainability reporting in practice and the impact that the upcoming Omnibus regulation will have on corporate sustainability reporting. Methodology: To analyze the level of sustainability reporting in practice, multiple case studies will be conducted based on selected companies, using the content analysis method. Findings: The research results indicate that companies report sustainability information in line with the requirements set by the CSRD. It is observable that the most detailed reporting is found in the social domain. Based on the research findings, it can be concluded that the existing NFRD and CSRD have influenced the level of sustainability reporting in practice. With the upcoming Omnibus regulation, which is expected to ease reporting requirements in practice, an impact on sustainability reporting is anticipated. Value: The main value of this research paper lies in the investigation of the impact of sustainability reporting legislation on sustainability reporting in practice. More specifically, the research examines the upcoming CSRD and the Omnibus regulation, analyzing how legislation influence is reported.